2019
DOI: 10.1186/s12943-019-1119-7
|View full text |Cite|
|
Sign up to set email alerts
|

m6A mRNA methylation regulates CTNNB1 to promote the proliferation of hepatoblastoma

Abstract: BackgroundN6-Methyladenosine (m6A) modification has been implicated in many biological processes. It is important for the regulation of messenger RNA (mRNA) stability, splicing, and translation. However, its role in cancer has not been studied in detail. Here we investigated the biological role and underlying mechanism of m6A modification in hepatoblastoma (HB).MethodsWe used Reverse transcription quantitative real-time PCR (RT-qPCR) and Western blotting to determine the expression of m6A related factors. And … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
130
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(136 citation statements)
references
References 32 publications
5
130
1
Order By: Relevance
“…36 Growing evidence shows that m 6 A contributes to the progression of cancer. Liu et al 37 demonstrated that enhanced m 6 A mRNA methylation plays an oncogenic mechanism role in hepatoblastoma. Yang et al 38 revealed that YTHDF2 was overexpressed in hepatocellular carcinoma cells and miR-145 modulates m 6 A levels by targeting the 3 0 -UTR of YTHDF2 mRNA in hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…36 Growing evidence shows that m 6 A contributes to the progression of cancer. Liu et al 37 demonstrated that enhanced m 6 A mRNA methylation plays an oncogenic mechanism role in hepatoblastoma. Yang et al 38 revealed that YTHDF2 was overexpressed in hepatocellular carcinoma cells and miR-145 modulates m 6 A levels by targeting the 3 0 -UTR of YTHDF2 mRNA in hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on other cell types and cancers have also reported connections between WNT signaling and m6A levels (Bai Y et al, 2019;Miao W et al, 2019;Han et al, 2020;Liu et al, 2019;Miao et al, 2019;Tang et al, 2020;Zhang et al, 2019). In some of these cases, m6A loss resulted in an elevation of WNT-signaling, while in others, it was diminished, and a variety of mechanisms have been proposed to explain these seemingly context-dependent effects.…”
Section: Discussionmentioning
confidence: 99%
“…METTL3 was considered to be a methyltransferase, part of the methyltransferase complex, and was responsible for the m6A modi cation [27,53].METTL3 was involved in many signal pathways such as PI3K / Akt [31,[54][55][56][57][58], MAPK [22] ,Wnt /beta-Catenin [47,59,60] and p38 / ERK [61]pathways,which were all associated with tumor deterioration. In addition, METTL3 could in uence the development of tumor by regulating some transcription factors or important oncogenes.Studies had found that METTL3 could positively regulate the expression of oncogene EZH2 [24,25,62].It promoted the expression of MYC as well as increased stability of protein by regulating the m6A methylation of MYC mRNA to lead to carcinogenesis in PCA and gastric cancer, promote the occurrence of OSCC tumor and affect the growth and invasion of BCA cells [40,[63][64][65][66].When METTL3 was silenced, it inhibited the activity of the Wnt pathway by reducing the m6A methylation level of LEF1 mRNA and reducing protein expression [59,67].…”
Section: Discussionmentioning
confidence: 99%